PENINGKATAN EFISIENSI RETRIBUSI PEMASARAN IKAN SEGAR TINGKAT PEDAGANG PENGUMPUL DI KECAMATAN KAMPA - Hasan, Samsurijal; Sari, Efti Novita; Aryadi, Aryadi; Suhud, Aris (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This service discusses the importance of increasing the efficiency of fresh fish marketing distribution at the level of intermediary traders in Kampa District. Fresh fish is one of the trade commodities that can be exported or sold domestically. The business of selling fresh fish is one of the business opportunities whose prospects are very bright, because fresh fish is one of the main consumptions of the Indonesian people. This business besides having a very wide range of consumers that this business can touch, i fish sales can be done in conventional and digital ways. Selling fish conventionally can be done by opening fish outlets in markets or in densely populated neighborhoods. Fish are not only sold to traditional markets both within the region (Kampar Regency) but can even be marketed to traders outside the region such as Pekanbaru City, Dumai City, Pelalawan Regency and Siak Regency. Fish traders as informal small entrepreneurs will always be faced with various limitations, especially the limitations of product continuity from fish farmers, facilities such as limited fleets and constraints in the implementation of distribution, such as travel time that is often disrupted due to rain, damaged roads and so on. Travel distance is very important because it is related to the durability of fresh fish and the cost of fuel oil (BBM). The problem that is often encountered is the obstacles on the way. The problem that is often encountered is the obstacles in traveling between the source of fish (fish farmers) to the intended market. For example, catfish is harvested around 21:00 to 22:00. The process of loading and distributing the number of fish for each destination market is about one to two hours and then starting the journey with the target of arriving at the destination market at 05.00 maximum. Distribution efficiency is the key to the success of the trader’s business. If the harvest time, travel time and condition of the fish when it arrives at the table trader, the profit that is targeted will be realized. If there is inefficiency, the collector traders will experience losses because the price per unit will drop significantly.